New annelid species from the deepest known whale-fall environment: Bathykermadeca thanatos sp. nov. (Annelida: Polynoidae) - Jimi, Naoto; Fujiwara, Yoshihiro; Kajihara, Hiroshi (Zootaxa, 2018)
A new species of polynoid annelids, Bathykermadeca thanatos sp. nov., is described based on specimens collected from sunken whale bones in the Nansei-Shoto Trench in the Philippine Sea at a depth of 4974 m. The cetacean-carcass community at the site exceeds the deepest record reported to date. This new species can be distinguished from other members of the genus by the following features: i) there is only one type of neurochaetae, ii) the teeth lack serration and grow inwardly, iii) median antenna extends beyond the tip of frontal filament, iv) nephridial papillae are present in segments 12–15, and v) there are about 50 notochaetae in each parapodium.